Exploring the link: nutritional status and chronic obstructive pulmonary disease - insights from NHANES and clinical research - Yang Yang; Manqing You; Wei Luo; Yang Xu; Lincheng Luo; Hailong Wei (BMC Pulmonary Medicine)
Abstract Background Malnutrition has been widely recognized as one of the critical modifiable determinants of adverse clinical outcomes in chronic obstructive pulmonary disease (COPD). However, the relationship between nutritional status and COPD across a broader population defined by lung function, as well as its association with acute exacerbations of COPD (AECOPD), remains unclear. Methods This study analyzed 3,591 participants with available lung function from the National Health and Nutrition Examination Survey 2007–2012. COPD was defined as a post-bronchodilator forced expiratory volume in one second (FEV1) to forced vital capacity (FVC) ratio below 0.70. Multivariable logistic and Cox regression were conducted to examine the relationship between nutritional status and COPD. Furthermore, cross-sectional data from consecutive AECOPD patients hospitalized at our institution from July 2024 to December 2024 were analyzed. Results In the NHANES study, participants with COPD exhibited poorer nutritional status than healthy controls. Body mass index (BMI) was associated with the presence of COPD (odds ratio [OR] 0.93, 95% confidence interval [CI] 0.929 to 0.931, p < 0.001) and all-cause mortality risk (OR 0.970, 95% CI 0.946 to 0.995, p = 0.019). When categorized by BMI levels, overweight had a lower risk of severe COPD (OR 0.394, 95%CI 0.307 to 0.507, p = 0.019) and all-cause mortality (OR 0.662, 95%CI 0.475 to 0.922, p = 0.015) compared to those with normal or underweight status. Other indicators, including malnutrition as defined by the geriatric nutritional risk index, as well as albumin and hemoglobin concentrations, were also associated with mortality in COPD participants. In the clinical research, the prevalence of malnutrition was approximately 48% in AECOPD. Malnourished patients not only presented with worse nutritional status but were also older, had more severe disease manifestations, and exhibited worse overall conditions. Moreover, nutritional indicators were significantly correlated with various clinical symptom scores in AECOPD. Conclusion Nutritional status may serve as a significant independent predictor of disease severity and clinical outcomes across the spectrum of COPD. Early implementation of systematic nutritional screening and nutritional interventions could potentially optimize clinical outcomes and modify disease progression in COPD.